Stem Cells, Hematopoiesis and Lineage Tracing: Transplantation-Centric Views and Beyond - Konturek-Ciesla, Anna; Bryder, David (Frontiers in Cell and Developmental Biology, 2022)
An appropriate production of mature blood cells, or hematopoiesis, is essential for organismal health and homeostasis. In this developmental cascade, hematopoietic stem cells (HSCs) differentiate into intermediate progenitor types, that subsequently give rise to the many distinct blood cell lineages. Here, we describe tools and methods that permit for temporal and native clonal-level HSC lineage tracing in the mouse, and that can now be combined with emerging single-cell molecular analyses. We integrate new insights derived from such experimental paradigms with past knowledge, which has predominantly been derived from transplantation-based approaches. Finally, we outline current knowledge and novel strategies derived from studies aimed to trace human HSC-derived hematopoiesis.